Determinan Minat Mahasiswa Akuntansi Dalam Pemilihan Karir Sebagai Akuntan Publik - Ismail, Nur Allief Yusuf; Syafei, Jasmina (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2024)
This research aims to determine the influence of job market considerations, financial rewards, family environment, openness to new things, professional training, intrinsic value of work, and social values ​​on Accounting students' interest in choosing a career as a Public Accountant. Sampling used a purposive sampling method, with a sample of 90 respondents. The analytical method used is the multiple linear analysis method. The research results prove that financial rewards, professional training, social values ​​influence accounting students' interest in choosing a career as a public accountant, while job market considerations, family environment, openness to new things, and intrinsic value of work do not influence accounting students' interest in choosing a career as a public accountant.